Translating Socioeconomic Status Between Nonhuman Primate and Human Studies in Health Research. (12th October 2020) - King, Rosalind B.; Paukner, Annika
Abstract: Evidence supports the proposition that early childhood adversity has long‐term health implications. Experimental research on the effectiveness of social policy interventions provides the gold standard of evidence but is difficult to obtain using humans. Animal models may play a role in generating a mechanistic evidence base, but researchers need appropriate models of socioeconomic status (SES). In this article, we discuss theoretical considerations for the development of appropriate animal models of SES to study its effect on health and development, emphasizing the literature on nonhuman primates. Focusing on the potential for translation between animal and human models, we define SES conceptually and outline its links to health. We then note demonstrated areas of equivalence and potential limits. We conclude with questions whose answers could help move the field forward.